2020
DOI: 10.1038/s41408-020-00356-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms associated with telomere length and risk of developing myeloproliferative neoplasms

Abstract: Telomere length measured in leukocyte (LTL) has been found to be associated with the risk of developing several cancer types, including myeloproliferative neoplasms (MPNs). LTL is genetically determined by, at least, 11 SNPs previously shown to influence LTL. Their combination in a score has been used as a genetic instrument to measure LTL and evaluate the causative association between LTL and the risk of several cancer types. We tested, for the first time, the "teloscore" in 480 MPN patients and 909 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Telomere length is at least in part genetically determined and there are several studies that have successfully used SNPs as genetic surrogates for telomere length to infer risk of developing several tumor types 23,[37][38][39][40][41][42][43][44][45] . This approach has never been attempted in MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomere length is at least in part genetically determined and there are several studies that have successfully used SNPs as genetic surrogates for telomere length to infer risk of developing several tumor types 23,[37][38][39][40][41][42][43][44][45] . This approach has never been attempted in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently genome-wide association studies (GWAS) have identified 11 SNPs 23,[34][35][36] that, collectively, explain 2.28% of LTL variability and can be used as a genetic instrument in a Mendelian randomization fashion. This approach has been already successfully tested in relation to the risk of developing various cancer types 23,[37][38][39][40][41][42][43][44][45] , but was never done in MM. We have tested the genetic score (henceforth called "teloscore") in the context of the International Multiple Myeloma rESEarch (IMMeNSE) consortium to investigate the relationship between gdTL and MM risk and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have confirmed that various loci associated with telomere length, including rs7705526 and rs2853677, are predisposing factors for MPN risk [ 103 ]. Specifically, an increased risk of MPN development was observed for individuals with longer telomere length measured in leukocyte (LTL), as determined using a combined “teloscore” from 11 telomere-length-associated SNPs [ 104 ]. The authors of the study concluded that longer telomeres are a risk marker for MPN development.…”
Section: Diagnosismentioning
confidence: 99%
“…A possible approach is suggested by the observation that LTL variability is under genetic control, and GWAS have identified 11 SNPs that predict LTL and therefore have been used as a surrogate for the direct measure of LTL and to evaluate the causative association between LTL and the risk of several human disease in large epidemiologic studies [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. We have called teloscore the score based on genetic determinants of LTL, as previously reported [ 47 , 48 ]. With these premises, our objective was to run a comprehensive study to investigate the role of STL and LTL in male infertility.…”
Section: Introductionmentioning
confidence: 99%